If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 2) + 4 = 26 Reorder the terms: 2(2 + 3x) + 4 = 26 (2 * 2 + 3x * 2) + 4 = 26 (4 + 6x) + 4 = 26 Reorder the terms: 4 + 4 + 6x = 26 Combine like terms: 4 + 4 = 8 8 + 6x = 26 Solving 8 + 6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 6x = 26 + -8 Combine like terms: 8 + -8 = 0 0 + 6x = 26 + -8 6x = 26 + -8 Combine like terms: 26 + -8 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| (2n+1)=3n^2 | | 5x+2x=75 | | (2x+1)=3n^2 | | 5*(x-1)+20=40*(x-3) | | 4B+36=3(20)-2B | | x(5-2x)=0 | | 3(m-2)=3(2m+3) | | x+0.3(150000)=150000 | | 2[x-7]=3x | | ln(x+2)=5 | | 102300+0.3x=x | | 2.3-n=4n-3.2 | | 6(t+8)-2t=3t-19 | | 72+2w=44 | | x^3-10x^2+33x-34=0 | | 3d+5=2d+6 | | 100000+0.3x=x | | 132418+0.3x=x | | 0.3x+25=x | | (47x+24y)+(35x+39y)= | | 13-10x=121-31x | | x*5=-8 | | 2s+3s-7m+2=17m | | m-7=-13+m | | 9x=8x-31 | | 42j+18-19=-28 | | 5y+8=2y+2 | | 5x=-2 | | 4(x+2)=4x-10 | | 3p-1=3x-9 | | 3x^2+12x= | | -4(1+5X)-7(-5+8X)=31 |